Elementi per una nuova fenomenologia dell’a priori culturale - Gonnella, Stefano (Bollettino Filosofico, 2018)
At the heart of the phenomenological method lies the move of epochè, whose residual should be caught by a phenomenologizing consciousness quite different from the natural consciousness involved in the intentional constitution of the world. However, this phenomenological residual is part and parcel of an intentional act performed by the phenomenologist as well. Thus, the filling of the eidetic structures unveiled by the epochè should correspond to a peculiar noema of this “catching intentionality”. The paper suggests to suspend the hidden belief in the absolute evidence of the residual of the epochè and to take on the issue of its cultural definition. This choice doesn’t mean to leave the phenomenological way, rather it requires to sharpen the analytical tools of phenomenology through a more radical performance of epochè (E. Fink, M. Henry, M. Richir), and to reintroduce the research about the still neglected cultural a priori (A. Gurwitsch, D. A. Conci, A. Steinbock) across phenomenological anthropology (M. Merleau-Ponty, A. Schütz, L. Embree).